2015
DOI: 10.1055/s-0034-1398779
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss einer posttraumatischen Belastungsstörung auf die Herzfrequenzvariabilität als Marker des autonomen Nervensystems – eine systematische Literaturübersicht

Abstract: In spite of the limitations, most of the studies have shown a relationship between PTSD and HRV. However, an assessment of this potential marker as a supplement for clinical diagnosis and therapy follow-up in patients with PTSD seems to be premature on the basis of the data obtained so far. Further research is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
1
7
0
2
Order By: Relevance
“…When excluding medicated patients, this pattern remained significant. Extending previous research (Meyer et al ., 2016), our findings indicate a significant impact of comorbid PTSD on HF-HRV, not only under baseline conditions but also during an ER task in BPD, pointing to complex interactions between (post)traumatic stress and autonomic nervous system functioning (Pechtel and Pizzagalli, 2011; Sammito et al ., 2015). Other variables that may affect HF-HRV, such as depressive symptoms, BPD symptom severity, and comorbidities other than PTSD did not differ between the patient groups, rendering it unlikely that they accounted for the observed group differences in HF-HRV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When excluding medicated patients, this pattern remained significant. Extending previous research (Meyer et al ., 2016), our findings indicate a significant impact of comorbid PTSD on HF-HRV, not only under baseline conditions but also during an ER task in BPD, pointing to complex interactions between (post)traumatic stress and autonomic nervous system functioning (Pechtel and Pizzagalli, 2011; Sammito et al ., 2015). Other variables that may affect HF-HRV, such as depressive symptoms, BPD symptom severity, and comorbidities other than PTSD did not differ between the patient groups, rendering it unlikely that they accounted for the observed group differences in HF-HRV.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced HRV has been linked to detrimental long-term effects on physical and mental health, including increased risk for immune dysfunction, inflammation, cardiovascular diseases (Liao et al ., 2002; Kemp and Quintana, 2013), major depression, anxiety (Kemp et al ., 2012; Chalmers et al ., 2014; Koenig et al ., 2016 a ), and PTSD (Pechtel and Pizzagalli, 2011; Sammito et al ., 2015; Meyer et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…People suffering from a series of psychiatric symptoms such as anxiety disorder 39 , panic attacks 39,40 , posttraumatic stress disorders 41 , epilepsy42, anorexia 43 , borderline personality disorder 44 and depressions 39,45,46 have been found to have lower HRV parameters.…”
Section: Psychiatric Diseasesmentioning
confidence: 99%
“…Consistent with this, low HF-HRV has been shown to be associated with both SUDs and post-traumatic stress. For example, a recent meta-analysis found that alcohol dependence was associated with lower HRV (Quintana, McGregor, Guastella, Malhi, & Kemp, 2013), and a meta-analysis of seven studies found lower resting HF-HRV in individuals with PTSD as compared to healthy controls (Chalmers, Quintana, Abbott, & Kemp, 2014; Sammito, Thielmann, Zimmermann, & Böckelmann, 2015). There are several plausible pathways linking HF-HRV to SUD and PTSD.…”
Section: Introductionmentioning
confidence: 99%